A kind of crack-resistant waterproof concrete containing modified polyacrylonitrile fiber and preparation method thereof
By adding epoxy soybean oil to the asphalt, grafting polyacrylonitrile fibers and combining them with water, cement, recycled aggregates, etc., forming a hydrophobic network and fiber-reinforced phase, the poor waterproof and crack resistance of traditional concrete are solved. The problem is that the strength and modulus of concrete have been significantly improved and safety hazards have been reduced.
Patent Information
- Application Number
- CN202311242674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-09-25
AI Technical Summary
Traditional concrete has poor waterproof and crack resistance, and low strength and modulus, resulting in safety hazards in building facilities.
The preparation method of crack-resistant waterproof concrete containing modified polyacrylonitrile fibers is adopted. Polyacrylonitrile fibers are grafted by adding epoxy soybean oil to the asphalt and compounded with water, cement, recycled aggregates, etc. to form a hydrophobic network and fibers. Reinforce the phase and improve the mechanical properties of concrete.
It significantly improves the waterproof and crack resistance of concrete, enhances the strength and modulus of concrete, reduces safety risks, and expands the potential of asphalt concrete in applications such as roads and bridge decks.
Smart Images

Figure BDA0004467922170000081 
Figure BDA0004467922170000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to a crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber and a preparation method thereof. Background Art
[0002] In recent years, the rapid development of infrastructure such as roads and steel box girder bridge decks in my country has led to an increasing demand for concrete. Traditional concrete has problems such as easy water absorption, poor crack resistance, low strength and modulus, which can lead to safety hazards in building facilities, so higher requirements are placed on the quality of concrete. Adding inorganic fibers, nanomaterials, organic polymer fibers, and asphalt to concrete can effectively improve the comprehensive performance of concrete.
[0003] Asphalt concrete is a building material made of asphalt, sand, gravel and aggregate. It has better water resistance, wear resistance and aging resistance, as well as good load-bearing capacity and anti-skid performance. It is widely used in road projects such as highways, expressways and airport runways. Polyacrylonitrile fiber has the characteristics of high strength and large modulus, and has broad application prospects in the field of building materials. Using polyacrylonitrile fiber to enhance and modify asphalt concrete is an effective strategy. However, the compatibility and bonding strength of polyacrylonitrile fiber with asphalt are poor, which will affect the mechanical properties of asphalt concrete. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a crack-resistant waterproof concrete containing modified polyacrylonitrile fiber and a preparation method thereof, which solves the problems of poor waterproof performance and crack resistance, as well as low strength and modulus of traditional concrete.
[0005] The technical solution provided by the present invention is:
[0006] A method for preparing crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber, comprising the following components in parts by weight: 18-25 parts of cement, 10-12 parts of water, 25-35 parts of sand, 20-35 parts of recycled aggregate, 6-12 parts of steel slag powder, 2-6 parts of matrix asphalt, and 0.1-0.5 parts of epoxy soybean oil grafted polyacrylonitrile fiber; the method for preparing crack-resistant and waterproof concrete comprises the following steps:
[0007] (1) The base asphalt is heated to 150-160°C for melting, and then the epoxy soybean oil grafted polyacrylonitrile fiber is added and stirred at high speed to obtain asphalt containing modified polyacrylonitrile fiber.
[0008] (2) The recycled aggregate is crushed, sorted and screened to obtain recycled aggregate with a particle size of 5-20 mm.
[0009] (3) Cement, sand, recycled aggregate, and steel slag powder are added to water, mixed evenly, and then asphalt containing modified polyacrylonitrile fiber is added, stirred at high speed, a standard test piece is cast, and cured at room temperature to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0010] Preferably, the stirring rate in (1) is 200-500 r / min, and the stirring time is 60-180 s.
[0011] Preferably, the stirring rate in (3) is 100-200 r / min, and the stirring time is 30-60 s.
[0012] Preferably, the preparation method of epoxy soybean oil grafted polyacrylonitrile fiber is:
[0013] S1. Plasma-treat high molecular weight polyacrylonitrile fiber in a plasma device, with a helium flow rate of 30-40 L / min and an oxygen flow rate of 0.7-1 L / min; then immerse the plasma-treated polyacrylonitrile fiber in an aqueous solution containing hydroxyethyl acrylate to carry out a grafting reaction, take out the fiber, and wash it with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0014] S2. Add hydroxyethyl acrylate grafted polyacrylonitrile fiber to dimethyl sulfoxide, heat to 60-70°C and stir for 1-3h, then reduce the temperature to 35-50°C, add epoxidized soybean oil and catalyst tin tetrachloride, react for 4-10h, cool, filter, wash with water and ethanol in sequence, and dry to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0015] Preferably, the mass fraction of the aqueous solution of hydroxyethyl acrylate in S1 is 25-40%.
[0016] Preferably, the grafting reaction in S1 is carried out at a temperature of 40-50° C. for 3-6 hours.
[0017] Preferably, the masses of the epoxidized soybean oil and tin tetrachloride in S2 are 4-12% and (0.1-0.35)% of the mass of the hydroxyethyl acrylate grafted polyacrylonitrile fiber, respectively.
[0018] The technical effect produced by the present invention is as follows: the present invention uses hydroxyethyl acrylate to perform plasma grafting on ultra-high molecular chain polyacrylonitrile, and then the introduced hydroxyl group undergoes a ring-opening reaction with the epoxy group of epoxidized soybean oil under the catalysis of tin tetrachloride to obtain epoxidized soybean oil grafted polyacrylonitrile fiber; then the epoxidized soybean oil grafted polyacrylonitrile fiber is compounded with asphalt to obtain asphalt containing modified polyacrylonitrile fiber; finally, it is compounded with water, cement, recycled aggregate, etc., poured, and cured to obtain crack-resistant and waterproof concrete.
[0019] The epoxy soybean oil grafted with high molecular weight polyacrylonitrile fiber in the present invention contains hydrophobic alkyl long chains and has better compatibility with asphalt. The asphalt containing modified polyacrylonitrile fiber forms a hydrophobic network in concrete, thereby improving the waterproof performance of the concrete.
[0020] The high molecular weight polyacrylonitrile fiber of the present invention has the advantages of high modulus and high strength, and is grafted with epoxy soybean oil containing long alkyl chains, which enhances the compatibility with asphalt, forms a fiber reinforcement phase in asphalt, and improves the mechanical properties of asphalt concrete; the asphalt containing polyacrylonitrile fiber has high adhesion with the minerals in concrete, which can improve the surface adhesion performance inside the concrete, and is conducive to enhancing the compactness, crack resistance, strength and modulus of the concrete. The practical application of asphalt concrete in roads, steel box girder bridge decks, etc. is expanded. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The preparation method of high molecular weight polyacrylonitrile fiber is prepared by referring to the method of "Study on Dry and Wet Forming Process and Fiber Properties of High Molecular Weight Polyacrylonitrile Fiber" in the journal "Synthetic Fibers", Volume 29, Issue 4.
[0023] Example 1
[0024] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 35 L / min and an oxygen flow rate of 1 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 25% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 40° C. for 4 h. The fiber is taken out and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0025] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 65°C and stirred for 1 hour, then the temperature is reduced to 40°C, 4 parts of epoxidized soybean oil and 0.1 parts of catalyst tin tetrachloride are added, reacted for 6 hours, cooled, filtered, washed with water and ethanol in sequence, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0026] (3) 2 parts by weight of base asphalt are heated to 160° C. for melting, and then 0.1 parts of epoxy soybean oil grafted polyacrylonitrile fiber are added, and stirred at high speed with a controlled rate of 200 r / min and a stirring time of 120 s to obtain asphalt containing modified polyacrylonitrile fiber.
[0027] (4) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0028] (5) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add the above-mentioned asphalt containing modified polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard test pieces, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0029] Example 2
[0030] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 35 L / min and an oxygen flow rate of 0.7 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 40% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 45° C. for 6 h. The fiber is taken out and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0031] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 70°C and stirred for 1 hour, then the temperature is reduced to 50°C, 8 parts of epoxidized soybean oil and 0.2 parts of catalyst tin tetrachloride are added, the reaction is carried out for 10 hours, cooled, filtered, washed with water and ethanol in sequence, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0032] (3) 3 parts by weight of base asphalt are heated to 155° C. for melting, and then 0.2 parts of epoxy soybean oil grafted polyacrylonitrile fiber are added, and stirred at high speed with a controlled rate of 300 r / min and a stirring time of 120 s to obtain asphalt containing modified polyacrylonitrile fiber.
[0033] (4) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0034] (5) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add the above-mentioned asphalt containing modified polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard test pieces, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0035] Example 3
[0036] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 30 L / min and an oxygen flow rate of 0.7 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 30% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 50° C. for 3 h. The fiber is taken out and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0037] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 60°C and stirred for 2 hours, then the temperature is reduced to 40°C, 10 parts of epoxidized soybean oil and 0.2 parts of catalyst tin tetrachloride are added, the reaction is carried out for 8 hours, cooled, filtered, washed with water and ethanol in turn, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0038] (3) 4 parts by weight of base asphalt are heated to 155° C. for melting, and then 0.3 parts of epoxy soybean oil grafted polyacrylonitrile fiber are added, and stirred at high speed with a controlled rate of 300 r / min and a stirring time of 60 s to obtain asphalt containing modified polyacrylonitrile fiber.
[0039] (4) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0040] (5) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add the above-mentioned asphalt containing modified polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard test pieces, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0041] Example 4
[0042] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 30 L / min and an oxygen flow rate of 1 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 40% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 40° C. for 6 h. The fiber is taken out and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0043] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 65°C and stirred for 2 hours, then the temperature is reduced to 40°C, 10 parts of epoxidized soybean oil and 0.28 parts of catalyst tin tetrachloride are added, the reaction is carried out for 8 hours, cooled, filtered, washed with water and ethanol in turn, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0044] (3) 5 parts by weight of base asphalt are heated to 155° C. for melting, and then 0.4 parts of epoxy soybean oil grafted polyacrylonitrile fiber are added, and stirred at high speed with a controlled rate of 300 r / min and a stirring time of 180 s to obtain asphalt containing modified polyacrylonitrile fiber.
[0045] (4) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0046] (5) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add the above-mentioned asphalt containing modified polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard test pieces, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0047] Example 5
[0048] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 30 L / min and an oxygen flow rate of 1 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 30% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 45° C. for 4 h, the fiber is taken out, and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0049] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 65°C and stirred for 2 hours, then the temperature is reduced to 40°C, 12 parts of epoxidized soybean oil and 0.35 parts of catalyst tin tetrachloride are added, the reaction is carried out for 8 hours, cooled, filtered, washed with water and ethanol in sequence, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0050] (3) 6 parts by weight of base asphalt are heated to 160° C. for melting, and then 0.5 parts of epoxy soybean oil grafted polyacrylonitrile fiber are added, and stirred at high speed with a controlled rate of 500 r / min and a stirring time of 180 s to obtain asphalt containing modified polyacrylonitrile fiber.
[0051] (4) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0052] (5) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add the above-mentioned asphalt containing modified polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard test pieces, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0053] Comparative Example 1
[0054] (1) High molecular weight polyacrylonitrile fiber is subjected to plasma treatment in a plasma device, with a helium flow rate of 35 L / min and an oxygen flow rate of 1 L / min; the plasma-treated polyacrylonitrile fiber is then immersed in an aqueous solution of 25% by mass of hydroxyethyl acrylate, and a grafting reaction is carried out at a temperature of 40° C. for 4 h. The fiber is taken out and washed with water and ethanol in turn to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber.
[0055] (2) 100 parts by weight of hydroxyethyl acrylate grafted polyacrylonitrile fiber is added to dimethyl sulfoxide, heated to 65°C and stirred for 1 hour, then the temperature is reduced to 40°C, 4 parts of epoxidized soybean oil and 0.1 parts of catalyst tin tetrachloride are added, reacted for 6 hours, cooled, filtered, washed with water and ethanol in sequence, and dried to obtain epoxidized soybean oil grafted polyacrylonitrile fiber.
[0056] (3) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0057] (4) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add 0.1 parts of epoxy soybean oil grafted polyacrylonitrile fiber, stir at high speed, control the stirring rate to 150r / min, the stirring time to 60s, cast standard specimens, and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0058] Comparative Example 2
[0059] (1) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with an average particle size of 10 mm;
[0060] (2) Add 20 parts of PO42.5 cement, 28 parts of sand, 30 parts of recycled aggregate, and 8 parts of steel slag powder to 11 parts of water by weight, mix well, add 2 parts of molten matrix asphalt, stir at high speed, control the stirring rate to 150r / min, and the stirring time to 60s. Cast a standard specimen and cure at room temperature for 28 days to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber.
[0061] Refer to the method of "JTJ E60-2008", take samples from the concrete core, and use the water permeability meter to test the water permeability coefficient of the concrete sample. The test structure is shown in the following table.
[0062]
[0063] As the weight percentage of asphalt containing modified polyacrylonitrile fiber gradually increases, the water permeability coefficient of the concrete in Examples 1-5 becomes smaller and smaller, and the waterproof performance becomes better and better. The epoxy soybean oil grafted with high molecular weight polyacrylonitrile fiber contains a hydrophobic alkyl long chain, which has better compatibility with asphalt and forms a hydrophobic network in the concrete, thereby improving the waterproof performance of the concrete. Comparative Example 1 only adds epoxy soybean oil grafted polyacrylonitrile fiber, and Comparative Example 2 only adds asphalt, and the water permeability coefficients are higher than those of the examples.
[0064] The mechanical properties of concrete samples were tested according to the methods of GB / T 50081-2002, GBJ 81-1985 and SL 352-2006. The test structure is shown in the following table.
[0065]
[0066] As the weight percentage of asphalt containing modified polyacrylonitrile fiber in the concrete in Examples 1-5 gradually increases, the high molecular weight polyacrylonitrile fiber has the advantages of high modulus and high strength, and is grafted with epoxidized soybean oil containing long alkyl chains, which enhances the compatibility with asphalt, forms a fiber reinforcement phase in the asphalt, and improves the mechanical properties of asphalt concrete; the asphalt containing polyacrylonitrile fiber has a high adhesion to the minerals in the concrete, which can improve the surface adhesion performance inside the concrete, and is beneficial to enhancing the density, crack resistance, strength and modulus of the concrete.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber, characterized in that: The anti-cracking and waterproof concrete comprises the following components in parts by weight: 18-25 parts of cement, 10-12 parts of water, 25-35 parts of sand, 20-35 parts of recycled aggregate, 6-12 parts of steel slag powder, 2-6 parts of matrix asphalt, and 0.1-0.5 parts of epoxy soybean oil grafted polyacrylonitrile fiber; the preparation method of the anti-cracking and waterproof concrete comprises the following steps: (1) heating the base asphalt to 150-160° C. to melt it, then adding the epoxy soybean oil grafted polyacrylonitrile fiber, and stirring at high speed to obtain asphalt containing modified polyacrylonitrile fiber; (2) crushing, sorting and screening the recycled aggregate to obtain recycled aggregate with a particle size of 5-20 mm; (3) adding cement, sand, recycled aggregate, and steel slag powder to water, mixing evenly, adding asphalt containing modified polyacrylonitrile fiber, stirring at high speed, pouring standard test pieces, and curing at room temperature to obtain crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber; The preparation method of the epoxy soybean oil grafted polyacrylonitrile fiber is as follows: S1. Plasma-treating high molecular weight polyacrylonitrile fiber in a plasma device, with a helium flow rate of 30-40 L / min and an oxygen flow rate of 0.7-1 L / min; then immersing the plasma-treated polyacrylonitrile fiber in an aqueous solution containing hydroxyethyl acrylate to carry out a grafting reaction, taking out the fiber, washing it with water and ethanol in sequence, to obtain hydroxyethyl acrylate grafted polyacrylonitrile fiber; S2, adding hydroxyethyl acrylate grafted polyacrylonitrile fiber to dimethyl sulfoxide, heating to 60-70°C and stirring for 1-3h, then reducing the temperature to 35-50°C, adding epoxidized soybean oil and catalyst tin tetrachloride, reacting for 4-10h, cooling, filtering, washing with water and ethanol in sequence, and drying to obtain epoxidized soybean oil grafted polyacrylonitrile fiber; The mass fraction of the aqueous solution of hydroxyethyl acrylate in S1 is 25-40%; The mass of the epoxidized soybean oil and tin tetrachloride in S2 is 4-12% and (0.1-0.35)% of the mass of the hydroxyethyl acrylate grafted polyacrylonitrile fiber, respectively.
2. The method for preparing crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber according to claim 1, characterized in that: The stirring rate in (1) is 200-500 r / min, and the stirring time is 60-180 s.
3. The method for preparing crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber according to claim 1, characterized in that: The stirring rate in (3) is 100-200 r / min, and the stirring time is 30-60 s.
4. The method for preparing crack-resistant and waterproof concrete containing modified polyacrylonitrile fiber according to claim 1, characterized in that: The grafting reaction in S1 is carried out at a temperature of 40-50° C. for 3-6 hours.
Citation Information
Patent Citations
Modified bamboo fiber reinforced asphalt mixture and preparation method thereof
CN113185191A
Permeable high-strength asphalt concrete and preparation method thereof
CN114149221A
Cited By
Polyacrylonitrile concrete as well as preparation method and application thereof
CN120081634A